Skill Up: A Software Developer's Guide to Life and Career - Hudgens, Jordan; Hudgens, Jordan (Packt Publishing, 2017)
This unique book provides you with a wealth of tips, tricks, best practices, and answers to the day-to-day questions that programmers face in their careers. It is split into three parts: Coder Skills, Freelancer Skills, and Career Skills, providing the knowledge you need to get ahead in programming.About This BookOver 50 essays with practical advice on improving your programming careerPractical focus gives solutions to common problems, and methods to become a better coderIncludes advice for existing programmers and those wanting to begin a career in programmingWho This Book Is ForThis book is useful for programmers of any ability or discipline. It has advice for those thinking about beginning a career in programming, those already working as a fully employed programmer, and for those working as freelance developers.What You Will LearnImprove your soft skills to become a better and happier coderLearn to be a better developerGrow your freelance development businessImprove your development careerLearn the best approaches to breaking down complex topicsHave the confidence to charge what you're worth as a freelancerSucceed in developer job interviewsIn DetailThis is an all-purpose toolkit for your programming career. It has been built by Jordan Hudgens over a lifetime of coding and teaching coding. It helps you identify the key questions and stumbling blocks that programmers encounter, and gives you the answers to them! It is a comprehensive guide containing more than 50 insights that you can use to improve your work, and to give advice in your career.The book is split up into three topic areas: Coder Skills, Freelancer Skills, and Career Skills, each containing a wealth of practical advice. Coder Skills contains advice for people starting out, or those who are already working in a programming role but want to improve their skills. It includes such subjects as: how to study and understand complex topics, and getting past skill plateaus when learning new languages. Freelancer Skills contains advice for developers working as freelancers or with freelancers. It includes such subjects as: knowing when to fire a client, and tips for taking over legacy applications. Career Skills contains advice for building a successful career as a developer. It includes such subjects as: how to improve your programming techniques, and interview guides and developer salary negotiation strategies.Style and approachThis unique book provides over 50 insightful essays full of practical advice for improving your programming career. The book is split into three broad sections covering different aspects of a developer's career. Each essay is self-contained and can be read individually, or in chunks.